Research on Operation Solutions Based on Computer Technology - Taking the Fruit Industry Sales as an Example - Li, Chao; Han, Jingrong (International Journal of Computer Science and Information Technology, 2024)
This paper applies computer technology to transform the fruit industry sales from traditional planting, processing, and sales models to intelligent, refined, and efficient operations through digital empowerment, refined management, and enhanced brand effect construction, thereby improving the operational efficiency and competitiveness of the entire industry chain. It is of profound and significant importance for promoting the transformation and upgrading of Shaanxi’s fruit industry, significantly improving fruit industry management efficiency, enhancing market competitiveness, actively promoting farmers’ income increase, and accelerating the sustainable development of the fruit industry.